A Fault Tolerant Model for Geometric Patterns of Swarm Agents - Rakesh, SK; Shrivastava, M (International Journal of Computer Sciences and Engineering, 2025)
Swarm robotics is based on the characteristics displayed by the insects and their colony and is applied to solve real world problems utilizing multi-robot systems. Research in this field has demonstrated the ability of such robot systems to assemble, inspect, disperse, aggregate and follow trails. A set of mobile and self-sufficient robots which has very restricted capabilities can form intricate patterns in the environment they inhabit. However, coordination of multiple robots to accomplish such tasks remains a challenging problem. Pattern formation is one of typical problems in the field of multi-robot cooperation. Compare to traditional multi-robot coordination algorithm, the method based on swarm robots to solve the issue of pattern formation has better scalability and dynamic adaptability and robustness. The swarm robots have only local perception and very limited local communication abilities, so one of the challenging tasks while designing swarm robotic systems with desired collective behaviour is to understand the effect of individual behaviour on the group performance. So fault tolerance is another issue to deal with. This paper reviews the background knowledge and some noticeable achievements in the field of pattern formation and fault tolerance